Methods of Mounting Saw-Toothed Metallic Wire on the Taker-in and Other Rollers of Carding Machine (GUB Journal of Science and Engineering, 2020)
Two methods are used for mounting sawtoothed metallic wire on different rollers of carding machine. The taker-in roller of the machine is generally grooved one way starting from one end of the roller to the other end and metallic toothed wires are mounted into the grooves. In course of time teeth of wires are worn out as they interact with fibers and impurities. As a result quality of product is deteriorated gradually. So the general practice is to replace the worn-out wires with new ones. Close observation of gradual wearing out of wire teeth reveals that due to oblique disposition of the teeth, only one of the two transitional edges of the front face of the teeth is mainly worn out leaving the other transitional edge intact. This paper explains one patented method and proposes another novel one that utilizes this unworn transitional edge and thus improves quality of yarn and increases longevity of the wear. The first method proposes taker-in with grooves starting from both ends of the roller. Application of this method will enable spinners to utilize both the transitional edges of taker-in teeth by dismounting the wires from the groove first after some use and then mounting the same wire on the roller again but into the grooves that start from other end of the roller. The second method proposes use of two types of wires on the bare taker-in roller; one type is toothed and another is without teeth. They are mounted on the roller side by side and alternately. Incorporation of tooth-less bare strip of wire gives obliqueness to the toothed wire. This method also will allow utilization of unworn edge of teeth by dismounting the wire first after some use and then mounting them on the roller starting from other end of it.GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 6(1), Dec 2019 P 27-32